Pelatihan Moodle Sebagai Aplikasi Learning Management System untuk Administrator Sekolah di SMA Negeri 18 Palembang - Rachmat, Nur; Devella, Siska; Meiriyama, Meiriyama (FORDICATE, 2024)
The Covid-19 pandemic requires every school to take innovative steps by utilizing technology in teaching and learning activities. Among various technological advancements in the world of education, Learning Management System (LMS) has emerged as a platform and Moodle is one of the most well-known and widely used LMS by educational institutions. Moodle has comprehensive features and is easy to understand for users. Through the Moodle LMS, educators can easily present comprehensive learning materials, create assessments, establish grading systems, track learning progress, view reports, and analyze learning outcomes. This technology is certainly desired to be adopted by State High School 18 Palembang to support a more effective learning process when conducted online. The schools action to support the smooth use of this LMS is to organize a training for school administrators. The training activities were attended by 5 staff members through direct practice methods, discussions and interactive question-and-answer sessions in the Computer Laboratory of Multi Data Palembang University.